Shape sensitivities for an inverse problem in magnetic induction tomography based on the eddy current model. (8th May 2015) - Hintermüller, Michael; Laurain, Antoine; Yousept, Irwin
Abstract: In this paper the shape derivative of an objective depending on the solution of an eddy current approximation of Maxwell's equations is obtained. Using a Lagrangian approach in the spirit of Delfour and Zolésio, the computation of the shape derivative of the solution of the state equation is bypassed. This theoretical result is applied to magnetic impedance tomography, which is an imaging modality aiming at the contactless mapping (identification) of the unknown electrical conductivities inside an object given measurements recorded by receiver coils.